The welfare state and the forces of globalization - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2007)
The emergence of the Asian tiger countries and the participation of the ex-communist countries in world trade has reduced the equilibrium price of labor in western Europe and elsewhere. However, the actual price of labor hardly reacts, because the welfare state's minimum replacement incomes are fixed. The rigidity of wages causes pathological overreactions of the European economy in terms of excessive capital exports, excessive immigration and excessive structural change towards the capital intensive export sectors. The overreactions cause unemployment, sluggish growth, a current account surplus and a high export volume, but may prevent gains from trade. To enable a more efficient economic reaction that would not jeopardize social goals but bring about more employment, growth and gains from trade, it is recommended to move the European welfare state from a system that primarily pays wage replacement incomes to one that pays wage subsidies.
Keywords: F11; F21; F22; H53; J64; 330; globalization; unemployment; welfare state; Globalisierung; Lohnniveau; Arbeitsmarktungleichgewicht; Soziale Lage; Lohnsubvention; Sozialstaat; Industriestaaten